Influence of Inter and Intra-Row Spacing on Hot Pepper (Capsicum Annum L.) Growth,Yield and Yield Component of Under Rain Fed at Guraferda and Gimbo, Southwest Ethiopia - Ashenafi Abriham (International Journal of Trends in Horticulture, 2024)
Inappropriate plant population density and other limitation factors are among the key reasons for the low hot pepper yield in Ethiopia, including South West Ethiopia. To increase the productivity of hot pepper use of appropriate population spacing is vital. Hence, a field experiment was conducted at Guraferda and Gimbo during the main rainy season to evaluate the response of hot pepper for growth and yield and yield components. A factorial arrangement of three inter-row spacings (50, 60, and 70 cm) and three intra-row spacings (30, 40, and 50 cm) was used in a randomized complete block design (RCBD) with three replications. Growth, yield, and yield component data were all recorded and statistically analyzed. The results indicated that, Number of pod per plant was significantly affected by both factors at Gimbo and Guraferda locations. Combined mean value also revealed that variation in interaction effect on number of pod per plant, marketable yield, Unmarketable yield, total dry pod yield. The highest marketable pod yield (1354.56 kg/ha and 1269kg/ha) was harvested from 60 cm inter-row spacing with 30 cm intra-row spacing (55,555 plants/ha) and 50 cm inter-row with 40 cm intra-row spacing (50,000plants/ha) respectively. Likewise the marketable pod yield, maximum total dried pod yield (1461.72 kg/ha and 1461.97kg/ha) was also obtained in 60cm inter-row and 30 cm intra-row spacing and 50 cm inter and 40 cm intra-row spacing respectively. As compared to national recommendation (70cm x 30cm), at 60cm x 30cm and 50cm x 40 cm there were 399.32kg/ha and 350.57kg/ha total dry pod yield increment. As a result of the high marketable pod yield and total dry pod yield, hot pepper producers in the research locations can benefit more from using 60cm inter-row spacing with 30cm intra row spacing and 50cm inter-row with 40cm intra-row spacing.
Keywords: Inter; Intra; Marketable; Spacing; Unmarketable